Sistem Keamanan Model Sidik Jari (Digital Key Security) Menggunakan Pemrograman Arduino Pada Sepeda Motor - Danang Yugo Pratomo (Universitas Negeri Malang, 2020)
Abstract: The fingerprint-type digital key model driving safety system offers an accurate security system in minimizing motorcycle units from potential theft crimes that are rampant. This study aims to develop a security system for a fingerprint model on a motorcycle using the arduino-based prototype development method. The test was carried out to determine the results of the arduino programming configuration on the board with a fingerprint scanner. Research results: 1) the design processed using the Arduino application shows that done compiling means that the configuration is successful. 2) The fingerprint scanning test results show that the ignition of the starter is faster when the palm of the finger is dry; that is, the average is activated 2.31 seconds. 3) The result of detection on unknown finger will be activate the alarm. Keywords: Security system, Fingerprint, Arduino application